Content Analysis of Verbal Violence in Film: Crows Zero, Crows Zero II, and Crows Zero Explode - Muhammad Wahyu Ibrahim; Dewi Soraya Rachmah; Lili Sugeng Wiyantoro (Cakra Communico: Journal of Communication Science, 2024)
This research aims to conduct a comprehensive analysis of the frequency and distribution of verbal violence in three films: "Crows Zero," "Crows Zero 2," and "Crows Zero Explode." The methodological approach employed is quantitative content analysis, allowing for the identification of various types of verbal violence such as harsh language, threats, insults, rating, scolding, and humiliation. All scenes depicting verbal violence in the three films constitute the research population. The findings of this study highlight the high frequency of verbal violence in the films, with the "weighting" indicator dominating in all three. Furthermore, the distribution of verbal violence also exhibits significant variations among the films, reflecting differences in character dynamics and storyline. Although verbal violence plays a crucial role in character development and narrative reinforcement, this research emphasizes that the representation of verbal violence in films does not always mirror reality. Instead, it is frequently utilized as a narrative tool to explore the complexity of interpersonal relationships and stimulate tension within the story. This study sheds light on a new understanding of how verbal violence is depicted in the context of films, emphasizing its essential role in shaping characters and weaving intricate narratives. Therefore, this research provides a richer insight into how verbal violence is represented.